2010
DOI: 10.1016/j.plasmid.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and prevalence of a fusobacterial plasmid

Abstract: Fusobacterium nucleatum is a Gram-negative anaerobic rod found in dental plaque biofilms, and is an opportunistic pathogen implicated in periodontitis as well as a wide range of systemic abscesses and infections. Genomic analyses of F. nucleatum indicate considerable genetic diversity and a prominent role for horizontal gene transfer in the evolution of the species. Several plasmids isolated from F. nucleatum, including pFN1, harbor relaxase gene homologues that may function in plasmid mobilization. In this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several plasmids of F. nucleatum , including pFN1, have relaxase gene homologs that may operate in plasmid mobilization. Recently, Claypool et al (41) found that the fusobacterial plasmid pFN1 encodes genes, enabling efficient mobilization between strains of Escherichia coli by the broad-range plasmid RP4. A role was suggested for plasmid mobilization in DNA transfer in F. nucleatum .…”
Section: Dna Transfer In Major Dental Plaque Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Several plasmids of F. nucleatum , including pFN1, have relaxase gene homologs that may operate in plasmid mobilization. Recently, Claypool et al (41) found that the fusobacterial plasmid pFN1 encodes genes, enabling efficient mobilization between strains of Escherichia coli by the broad-range plasmid RP4. A role was suggested for plasmid mobilization in DNA transfer in F. nucleatum .…”
Section: Dna Transfer In Major Dental Plaque Bacteriamentioning
confidence: 99%
“…A role was suggested for plasmid mobilization in DNA transfer in F. nucleatum . Plasmid or plasmid-related sequences were identified in as many as 11.5% of the strains in a panel of clinical F. nucleatum isolates (41). Roberts and Lansciardi (42) showed that two strains of F. nucleatum were able to transfer tetracycline resistance by conjugation encoded by the tet (M) determinant to strains of F. nucleatum , Peptostreptococcus anaerobius , and Enterococcus faecalis .…”
Section: Dna Transfer In Major Dental Plaque Bacteriamentioning
confidence: 99%
“…polymorphum (Fnp 10953; transformation by electroporation) 52 , Fusobacterium nucleatum subsp. polymorphum 12230 ( Fnp 12230; transformation by sonoporation) 53 , and a recent paper highlighting the first gene interruption in Fusobacterium necrophorum using DNA conjugation from E. coli 54,55 . Needless to say, these four strains do not encompass all of the Fusobacterium subspecies and their respective infections and diseases that we would like to study and highlights the need for molecular biology and biochemical studies to achieve universal genetics.…”
Section: Introductionmentioning
confidence: 99%